2019
DOI: 10.1177/1043454219849583
|View full text |Cite
|
Sign up to set email alerts
|

Back to Basics: CLABSI Reduction Through Implementation of an Oral Care and Hygiene Bundle

Abstract: Children with cancer often undergo treatments that render them severely immunocompromised. Side effects of treatment place them at risk for developing oral mucositis (OM), which can potentially lead to infection and bacteremia. Staff nurses on an inpatient pediatric oncology unit noted inconsistent daily oral hygiene practices despite assessing OM consistently. Basic oral hygiene can reduce the severity of OM, and evidence-based bundled care has shown to increase consistency of practice. Based on findings and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…This inexpensive and nonirritating solution seems our best option. Kemp et al (2019) identified nurse-to-patient ratios as a contributing factor to adherence to following CVC care and hygiene recommendations. Our spike in CLABSI events occurred during a period of high sick leave utilization among hematology/oncology staff and the need to use rotational staff support from other services within the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…This inexpensive and nonirritating solution seems our best option. Kemp et al (2019) identified nurse-to-patient ratios as a contributing factor to adherence to following CVC care and hygiene recommendations. Our spike in CLABSI events occurred during a period of high sick leave utilization among hematology/oncology staff and the need to use rotational staff support from other services within the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown how comfort/talk with patient and educating patients and families are instrumental in various settings (from pediatric intensive care to pediatric hematology-oncology) 31,32 . In addition, performing oral hygiene reduces the risk of central line–associated bloodstream infection and should be provided throughout the patient’s hospital stay 13 . Also preparing patients and families for discharge is important throughout hospitalization, because there is evidence that the presence of a nurse discharge specialist enables to reduce the number of activities to be carried out, thus facilitating the transition from hospital to home 33 …”
Section: Discussionmentioning
confidence: 99%
“…Unlike some previous studies, 7,24,36 our study provides a focus on single activities and a starting point for a more effective management of this phenomenon. This is essential from an organizational and managerial perspective because it enables nursing leaders to act on the weaknesses of their units and address the activities that have the most negative effects on patient outcomes 2,4,5,11–13,25,38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaughan et al 11 retrospectively examined their CLABSI events to determine whether standard bundle protocols for central line care would reduce MBI-LCBI events and found a reduction in both MBI-and non-MBI-related events. Furthermore, Kemp et al 12 recently published their attempts to reduce CLABSI events through oral care and hygiene. Through the implementation of an oral care bundle alone, they were able to demonstrate a significant reduction in both MBI and LCBI events.…”
Section: Discussionmentioning
confidence: 99%